2001
DOI: 10.1128/jcm.39.3.836-843.2001
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus Strain Diversity in Blantyre, Malawi, from 1997 to 1999

Abstract: In a 2-year study of viral gastroenteritis in children in Blantyre, Malawi, the diversity of rotavirus strains was investigated by using electropherotyping, reverse transcription-PCR amplification of the VP7 and VP4 genes (G and P genotyping), and nucleotide sequencing. Of 414 rotavirus strains characterized, the following strain types were identified: P[8], G1 (n ‫؍‬ 111; 26.8%); P[6], G8 (n ‫؍‬ 110; 26.6%); P[8], G3 (n ‫؍‬ 93; 22.5%); P[4], G8 (n ‫؍‬ 31; 7.5%); P[8], G4 (n ‫؍‬ 21; 5.1%); P[6], G3 (n ‫؍‬ 12; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
140
4
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(155 citation statements)
references
References 59 publications
8
140
4
3
Order By: Relevance
“…Some of these may only have local significance (e.g. G5 in parts of Brazil and G8 in Malawi; Bok et al, 2001b;Cunliffe et al, 2001b), but at least one serotype, G9, was demonstrated to have dispersed worldwide (Ramachandran et al, 1996;Unicomb et al, 1999;Griffin et al, 2000;Iturriza-Gó mara et al, 2000;Palombo et al, 2000;Araú jo et al, 2001;Bok et al, 2001a;Cunliffe et al, 2001a;Bányai et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these may only have local significance (e.g. G5 in parts of Brazil and G8 in Malawi; Bok et al, 2001b;Cunliffe et al, 2001b), but at least one serotype, G9, was demonstrated to have dispersed worldwide (Ramachandran et al, 1996;Unicomb et al, 1999;Griffin et al, 2000;Iturriza-Gó mara et al, 2000;Palombo et al, 2000;Araú jo et al, 2001;Bok et al, 2001a;Cunliffe et al, 2001a;Bányai et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Such genetic diversity is recognised to be generally greater in developing countries including African countries than in industrialised countries [10,11,31]. Malawi, which has historically harboured a rich diversity of circulating rotaviruses [15,16] was selected as a site for a pivotal clinical trial of a human, monovalent G1P [8] rotavirus vaccine, Rotarix [8]. In the trial in Malawi, the diversity of circulating rotavirus strains was greater [8] than in any previously published rotavirus vaccine trial, in which the globally most common G1P [8] strain has predominated [32].…”
Section: Discussionmentioning
confidence: 99%
“…MAL23 (G1P [8]) and MAL82 (G9P [8]) belonged to lineage IV, whereas RIX4414 belonged to lineage II. The P [8] VP4 genes carried by Malawian strains reported previously belonged to lineages I, III and IV [15], and thus despite the same geographical origin, Malawi P [8] VP4 genes were noted to be highly divergent. In the P[6] VP4 phylogenetic tree there were 5 lineages (Fig.…”
Section: Phylogenetic Analysis Of Vp7 Vp4 Vp6 and Nsp4 Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…19 We therefore, analysed 72 paired serum samples for neutralising activity against 3 human (Rotarix G1P [8], MW333 G8P [4] and WI61 G9P [8]), 1 bovine (WC3 G6P [5]) and 2 bovine-human reassortant (RotaTeq G1P [5] and G6P [8]) rotavirus strains, using MN assay ( Table 2). We found that children with natural infection developed high titres of cross-reactive neutralising activity responses against homotypic and heterotypic human strains.…”
mentioning
confidence: 99%